2013
DOI: 10.7314/apjcp.2013.14.3.1747
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Smoking Initiation and Susceptibility to Future Smoking among School-Going Adolescents in Lagos State, Nigeria

Abstract: Background: It is projected that low and middle-income countries will bear a major burden of tobacco related morbidity and mortality, yet, only limited information is available on the determinants of smoking initiation among youth in Africa. This study aimed to assess the determinants of smoking initiation and susceptibility to future smoking among a population of high school school students in Lagos, Nigeria. Materials and Methods: Baseline data from an intervention study designed to assess the effect of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
55
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 18 publications
22
55
1
Order By: Relevance
“…Among the 9.85% of children those have reported smoking habit, the main tobacco product consumed is cigarette and none of them used the hand rolled beedis. Similar tobacco use pattern were reported from a study conducted in Lagos (Odukoya et al, 2013).This preference towards branded cigarettes illustrates the fact that cigarette smoking has more acceptances among school children even in rural areas. The practice of chewing betel quid has much significance attached to it in India.…”
Section: Discussionsupporting
confidence: 64%
“…Among the 9.85% of children those have reported smoking habit, the main tobacco product consumed is cigarette and none of them used the hand rolled beedis. Similar tobacco use pattern were reported from a study conducted in Lagos (Odukoya et al, 2013).This preference towards branded cigarettes illustrates the fact that cigarette smoking has more acceptances among school children even in rural areas. The practice of chewing betel quid has much significance attached to it in India.…”
Section: Discussionsupporting
confidence: 64%
“…This is corroborated by findings done in the southwestern Nigeria by Ayo-Yusuf where majority of the adults were observed to be light smokers [13] and in other environments where youth were also more often light smokers [14][15][16]. This may be because they may not have the economic capacity to purchase many cigarettes [17] which is buttressed by the fact that almost half of the respondents in this study were beggars.…”
Section: Discussionsupporting
confidence: 85%
“…Approximately 80% of adult smokers begin smoking before 18 years (Philip et al, 2013). Studies on students of Nigeria, India, and Turkey indicate that being male and having parents or friends who smoke were more likely to initiate smoking (Golbasi et al, 2011;Muttappallymyalil et al, 2012;Odukoya et al, 2013;Ozturk et al, 2011). A study with 3, 706 undergraduate students from seven universities in England, Wales, and Northern Ireland found that smoker was low income, or those fathers had at least a bachelor degree, and binge drinkers (Ansari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%